2022
DOI: 10.21071/psye.v14i1.14168
|View full text |Cite
|
Sign up to set email alerts
|

Ciber-rumor y síntomas internalizantes en la adolescencia: efecto mediador de la resiliencia

Abstract: Los dispositivos digitales han adquirido un papel fundamental en las dinámicas sociales entre los adolescentes, aumentando la prevalencia de conductas de riesgo como el ciberacoso. Aunque su estudio ha aumentado en las últimas décadas, aún son escasos los trabajos centrados en conocer los efectos de formas de cibervictimización sutiles, como el ciber-rumor. Los objetivos del estudio fueron, primero, examinar si las víctimas de ciber-rumor presentan mayores niveles de síntomas internalizantes, y segundo, explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although some questions were answered, more research is needed to better understand the factors related to a greater compliance in adolescents to promote social well-being. For example, compliance could be related to online interpersonal interactions, and problem behaviors such as cyberbullying and cybergossip (Bravo et al, 2022) should be explored in relation to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Although some questions were answered, more research is needed to better understand the factors related to a greater compliance in adolescents to promote social well-being. For example, compliance could be related to online interpersonal interactions, and problem behaviors such as cyberbullying and cybergossip (Bravo et al, 2022) should be explored in relation to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding resilience as the ability to be strong in traumatic or crisis situations, such as the global pandemic we find ourselves in, it can be considered as a fundamental competence for developing emotional intelligence (Alvarado, 2015;Belykh, 2018;Bravo et al, 2022;Nuñez & Luzurraga, 2017). Given this situation, we believe it is important to carry out research on the relationship between EI and resilience in secondary school adolescents during times of global pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience, understood as the ability to absorb stressful situations, is one of the strategies used to improve the well-being of university students [35]. Promoting a culture of resilience in the learning environment and programmes aimed at fostering well-being and student care were initiatives carried out with medical students to great effect [36,37]. In this respect, Neufeld et al [35] found that medical students who are resilient perceive SBPN, whereas those who have not acquired a culture of resilience feel FBPN.…”
Section: Introductionmentioning
confidence: 99%